World Christianity in Muslim encounter essays in memory of David A. Kerr - Kerr, David A.; Goodwin, Stephen R. (London ; New York : Continuum, 2009)
Global Christianity in Local Context and Muslim Encounter is a unique collection of essays in honour of David A. Kerr, well-known for his contributions in the areas of Christian-Muslim dialogue, Ecumenical Studies and Missions. With contributions from recognized experts in these fields, the book provides a platform for examining contemporary Christian-Muslim relations and critical issues facing twenty-first century Christianity. Volume 2 is a veritable Who's Who of renowned Christian and Muslim scholars that have shaped the course of Christian-Muslim dialogue over the last half century. Their
1. Islam Hostage to Itself?, Kenneth Cragg (Bishop, Jerusalem Archdiocese; University of Oxford, UK); 2. Seeking to Overcome Islamaphobia Through Education and Dialogue, John B. Taylor (World Council of Churches, World Conference on Religion and Peace; International Association for Religious Freedom); 3. Interreligious Challenges in Europe's Cities, Anton Wessels (Free University of Amsterdam, The Netherlands); 4. Christians, Muslims and Religious Freedom: A Christian Perspective, David Marshall (Inter-Faith Relations, UK, on behalf of the Archbishop of Canterbury); 5. The Abrahamic Faiths in their New Context, David B. Burrell (University of Notre Dame, USA / Uganda Martyrs University, Uganda); 6. Christians and Muslims in the Qur'an and Muslim Tradition, Mahmoud Ayoub (Temple University, USA); 7. Open Letter from Muslim Ulema to Christian Leaders, Jacques Waardenburg (Professor Emeriuts, University of Lausanne, Switzerland); 8. Recent Developments in Christian-Muslim Relations, Hugh Goddard (University of Nottingham, UK); 9. Modern Muslim Perceptions of the Crusades, Carole Hillenbrand (University of Edinburgh, Scotland); 10. Christian-Muslim Relations in Ethiopia: Lessons from the Past, Opportunities for the Future, F. Peter Ford, Jr (Mekane Yesus Seminary, Ethiopia); 11. The Changing Face of Islamists in Sudan, Edward Riak Kajivora (Bible Translation Consultant for the Bible Society of Sudan, Khartoum); 12. Dialogue and the Challenges of Truth in Christendom and Islam, Christian Troll (Philosophical-Theological Academy, St George, Frankfurt/Main, Germany); 13. Forgiveness and Reconciliation through the lenses of the Bible and the Qur'an, Sigvard von Sicard (University of Birmingham, UK); 14. Re-forming American images of Muslims -- A View from the Trenches, Robert Hunt (Perkins School of Theology, Southern Methodist University, USA); 15. Abrogation in the Qur'an, Christopher Lamb (formerly Inter-Faith Relations Advisor to the Church of England); 16. Christian-Muslim Dialogue: Mirage or Destiny?, Khurshid Ahmad (Honorary Professor of Islamic Economics, Pakistan); 17. Debates on Jesus and Muhammad in Europe, India and Pakistan, Jan Slomp (National Advisor for Relations with Islam, Reformed Churches of the Netherlands); 18. Europe and the Arab World in the Twentieth Century: Behind the Myths of the 'West' and 'Islam', Jorgen S. Nielsen (University of Copenhagen, Denmark / University of Damascus, Syria); 19. Christian-Muslim Relations in Africa, With a Focus on Nigeria, Klaus Hock (University of Rostock, Germany); 20. 'For the Good of the City: Bradford -- A Case Study in Inter-Community Relations, Philip Lewis (University of Bradford, UK). 21. The Selly Oak Centre: An Enduring Vision Seeking Fulfilment, Chris Hewer (St Ethelburga Centre, UK).
"Publications by David A. Kerr": p. [345]-346.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Religion; RELIGION -- Christianity -- General; RELIGION -- Christian Life -- Social Issues; Electronic books